The impact of indocyanine-green fluorescence angiography on intraoperative decision-making and postoperative outcome in free flap surgery - Bigdeli, Amir Khosrow; Thomas, Benjamin; Falkner, Florian; Gazyakan, Emre; Hirche, Christoph; Kneser, Ulrich (Journal of reconstructive microsurgery, 2020)
Background: Reliable perfusion of the distal portions of free flaps is decisive for the reconstructive success. Indocyanine green near-infrared video angiography (ICG-NIR-VA) has been adopted for objective assessment of free flap tissue perfusion but is thus far not used on a routine basis. Therefore, we investigated its intraoperative impact on decision-making and postoperative outcome. Methods: From January 2017 to June 2019, 88 consecutive adipo- or fasciocutaneus free flaps were performed in conjunction with intraoperative ICG-NIR-VA. Free flap tissue perfusion was first assessed clinically and then compared with ICG-NIR-VA findings. Based on the results, the decision for intraoperative trimming of critically perfused flap zones was made. The way of decision-making, flap success, and failure rates as well as intra- and postoperative complication rates were analyzed. Results: The overall free flap success rate was 92.0%. Partial flap necrosis occurred in five cases (5.7%) and total flap necrosis in two cases (2.3%). ICG-NIR-VA aided decision-making and flap design in 34 cases (38.6%) and led to complication-free postoperative courses. When ICG-NIR-VA was relied on (82 out of 88 flaps; 93.2%), there was no unpredicted postoperative tissue necrosis (overestimation). When ICG-NIR-VA was not relied on (6 out of 88 flaps; 6.8%), there were five cases of postoperative partial flap necrosis and one case of uneventful healing (underestimation). The sensitivity of ICG-NIR-VA was 100% (95% confidence interval [CI]: 64.6-100) and the specificity was 98.8% (95% CI: 93.3-100) with a positive predictive value of 87.5% (95% CI: 52.9-99.4) and a negative predictive value of 100% (95% CI: 95.4-100). Conclusion: Intraoperative ICG-NIR-VA objectified free flap perfusion and thus refined surgical decision-making on flap design in all cases. It could always predict tissue necrosis and subjectively improved outcomes in free flap surgery at our institution. Furthermore, it could be easily implemented in intraoperative routine, only adding minimal additional operative time.
Gesehen am 28.09.2020